Quality of Administrative Services and Campus Infrastructure on Student Satisfaction with Student Loyalty as Intervening Variables at The Faculty of Administrative Science Universitas Brawijaya - Nadya Naulanda; Siti Rochmah; Alfi Haris Wanto (Sekolah Pascasarjana Universitas Brawijaya, 2022)
Student satisfaction is important for some students besides student loyalty which can be influenced by several factors, one of which is the quality of service and infrastructure which students are also expected to create a good campus atmosphere. This study aims to determine whether the quality of service and infrastructure has an effect on student satisfaction through student loyalty at the Faculty of Administrative Sciences, Universitas Brawijaya Malang. This research method is a quantitative method using SPSS 22 for Windows. The type of data collection used is primary data in the form of data collected through filling out questionnaires distributed to 100 students using a research scale, namely the Likert scale. The data analysis used is path analysis. , validity test, reliability test, classical assumption test, Sobel test, F test, and t test. The results of this study indicate that the value of t count (2.115 and 2.403 ) > t table (1.984), F arithmetic value (60.685 and 25.923) > F table (3.09). This means that either simultaneously or partially there is a significant influence on service quality and infrastructure has a direct influence on student satisfaction, service quality and infrastructure have a direct influence on student loyalty. Student loyalty as an intervening variable can mediate the indirect effect of service quality and infrastructure on student satisfaction.